2009
DOI: 10.1073/pnas.0811829106
|View full text |Cite
|
Sign up to set email alerts
|

Statistical estimation of cell-cycle progression and lineage commitment in Plasmodium falciparum reveals a homogeneous pattern of transcription in ex vivo culture

Abstract: We have cultured Plasmodium falciparum directly from the blood of infected individuals to examine patterns of mature-stage gene expression in patient isolates. Analysis of the transcriptome of P. falciparum is complicated by the highly periodic nature of gene expression because small variations in the stage of parasite development between samples can lead to an apparent difference in gene expression values. To address this issue, we have developed statistical likelihood-based methods to estimate cell cycle pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
138
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(143 citation statements)
references
References 29 publications
(39 reference statements)
5
138
0
Order By: Relevance
“…Gene level log 2 (Cy5/Cy3) expression ratios were computed from probe level values using median polish. We calculated the most likely time post-invasion along the asexual cycle for each sample using a statistical likelihood method (Lemieux et al 2009), with the HB3 transcriptome as reference (Bozdech et al 2003). Expression values for each gene [log 2 (Cy5/Cy3)] were plotted against estimated times for each parasite line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene level log 2 (Cy5/Cy3) expression ratios were computed from probe level values using median polish. We calculated the most likely time post-invasion along the asexual cycle for each sample using a statistical likelihood method (Lemieux et al 2009), with the HB3 transcriptome as reference (Bozdech et al 2003). Expression values for each gene [log 2 (Cy5/Cy3)] were plotted against estimated times for each parasite line.…”
Section: Discussionmentioning
confidence: 99%
“…To account for this, we estimated the stage of the cycle for each microarray sample using a statistical likelihood-based method (Supplemental Fig. S1; Lemieux et al 2009) and plotted expression levels against estimated times post-invasion (Fig. 1C,D).…”
Section: Identification Of Genes Under Clonally Variant Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomes of both parasites have been sequenced; however, genome data from clinical isolates of both parasites are limited [6,7]. Analyses of transcriptome in clinical samples of Pf as well as Pv have been carried out [8][9][10][11]. A recent study has categorized the malaria patients on the basis of the differences in transcriptome profiles exhibited by the parasites they harbored [10].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, earlier studies sought to associate the expression of particular parasite genes or proteins with disease severity by comparing the transcriptome and proteome of parasites obtained from different types of malaria episodes. Two recent DNA microarray studies failed to identify parasite genes whose expression was related to disease severity (13,14). In contrast, microarray and proteomic studies of pregnancy malaria have identified sets of genes and proteins, including VAR2CSA, that are more abundant in parasites isolated from pregnant women than in those from children (15,16) or that are more abundant in placental parasites than in a laboratory-adapted reference strain (17).…”
Section: Introductionmentioning
confidence: 99%